The Effect of Physical Activities on Physical Education Learning Outcomes - Eva Julianti P; Firmansyah Dlis; Moch Asmawi (Kazimierz Wielki University, 2019)
This study aimed to find the effect of physical activity on academic performance of physical education. The research method used in this research is quantitative approach, survey method with test and measurement technique. The population of the research was students at a public secondary school in East Jakarta, and 216 students of 6 classes grade eight participating in this research. There is a positive influence of physical activity on student learning outcome of physical education. Physical activity has a direct positive effect on learning outcomes of physical education. This means that increasing physical activity will lead to an increase in physical education learning outcomes. Implication of the present study is that efforts can be made to improve learning outcomes physical education through structured physical activity, by providing physical activities, games and sports chosen to achieve educational goals.